Dampak Covid 19 Terhadap Perubahan Harga Saham Perbankan di Indonesia Sebelum dan Saat Pandemi - Recha Silvilia Lorenza; Ria Octavia; Shafitranata Shafitranata; Asri Winanti Madyoningrum (Penerbit Goodwood, 2022)
Purpose: Aims of this research to examine the differences among internal and external factors that affect stock prices before and during the Covid-19 pandemic. Methodology: Research methods uses a quantitative approach method, obtained as many as 18 banks registered at IDX for 2016-2021. Data were processed using the Wilxocon sign test and the paired sample t test using SPSS software. Results: The results show a significant difference, during a pandemic ROA decreased by 1.3%, ROE decreased by 1.91%. Hypothesis testing using paired sample t test on the DER, exchange rate, and interest rates variables show significant differences before and during the Covid-19 pandemic. During the pandemic, DER increased by 0.03%, the exchange rate decreased by 0.02%, and interest rates decreased by 0.13%. Limitations: This research found that there was an influence on banking stock prices before and during the pandemic, as well as significant differences in stock prices. This research is also limited by using a sample of 19 companies in the banking sector that are listed on the IDX. Contribution: This research is expected to be input for banks in managing stocks properly and considering the Covid-19 pandemic. Research contribution to the field of science through the management of stock prices before and during the pandemic.